Design And Development Of Dc-Dc Boost Converter Based On Dsp Tms320f2812 For Pv Application - Jubair Al-Hiealy, Mohammed Rasheed; Omar, Rosli; Sulaiman , Marizan (Indian Society Of Education And Environment & Informatics Publishing Limited, 2016)
Objective: In this paper, we reported experiment control voltage signal of Pulse Width Modulation (PWM) design circuit of closed loop implemented of dc-dc boost converter for application Photovoltaic (PV) simulator. Methods/Statistical Analysis: In this design, the converter provides step-up voltage from the PV generating systems as an interface between the load and PV panel and let the follow-up of the Findings: The operation was performed obased on a specifically associated converter to the PV panel which is controlled via the observed P&O and Maximum Power Point Tracking (MPPT) perturb. The regulation is achieved by PWM at a fixed frequency and the switching device is generally Insulated Gate Bipolar Transistor IGBT. Application/Improvements: The feedback path is established with a control circuit such that a proper duty cycle is achieved for the desired output voltage (Vo) for the application photovoltaic generating systems. The proposed scheme is modelled to utilise MATLAB/SIMULINK and verified through simulation result, and prototype experiment for the purpose of utilising the Digital signal processing (DSP) TMS320F2812 control PWM.